Villainized subjects in the first-wave COVID-19 crisis in English online news in Thailand - Thongpanich, Pancharle (Journal of Language and Culture, 2024)
This paper discusses the narrative construction of “villains'' in COVID-19 Thai online news, proposing that media portrayals of subjects related to COVID-19 were negatively framed as villains through narrative framing and biased characterization. A close critical reading method, aided by Vladimir Propp’s narratological model and Michel Foucault’s theoretical conceptions of power and knowledge, is used in the analysis of the texts. The article includes the definition of ‘villains’, the villainization process, and the villainized subjects in COVID-19 English online news during the first wave crisis in Thailand in the first half of 2020. By doing so, this paper aims to provide a clearer understanding of past perspectives on the pandemic and its moral repercussions for Thai society in order to strengthen communication and response strategies when interacting with COVID-19 subjects and victims of future pandemics.